Edukacja obywatelska w świetle współczesnych przemian koncepcji obywatelstwa w państwie narodowym - Hildebrandt-Wypych, Dobrochna (Wydawnictwo Naukowe UAM, 2012)
The general aim of the article is to describe the infl uence of diverse interpretations of citizenship in a pluralistic society on the new meanings of citizenship education a contemporary nation-state. The eoretical background for the study is the social constructivist perspective. The article begins with the brief description of the multidimentional infl uence of globalization on a nation-state and citizenship, followed by the discussion on one of its key consequences: the shifting concept of itizenship in the – currently in crisis – European nation-state and welfare state. The key research question of the article concerns the infl uence of the growing diversity and fl exibility of the citizenship ideals and norms on citizenship education. What citizen is the contemporary school supposed to shape and what are the current challenges and development paths within citizenship education? The answers to these questions are searched with reference to the T. McLaughlin conception of maximal minimal citizenship and the interpretative character of the democratic citizenship. One of the key controversies concerning school as a place for learning democracy is the balance between – on one side – equipping young people with the socially and culturally adequate knowledge and skills for „a good citizenship” and – on the other – developing a sense of national community around a shared common identity. The clash between the minimal and maximal (including e.g. global citizenship ideas) concept of citizenship education brings up the necessity for the educational consensus on the virtues recognized in the public sphere, especially in the light of the growing social, ethnical and cultural diversity in contemporary societies. The growing interconnectedness of national and global citizenship leads to the more advanced (deeper) understanding of the latter: not only as an ethical concept, but also as a practical way of participating in a liberal democracy.
Citizenship education in the light of current changes of the citizenship concept in the nation-state
Keywords: citizenship; nation-state; citizenship education; liberal democracy; global citizenship